Management of MRSA patients on the dental chair - Manjunath, Nandini; Banu, Faima; Chopra, Aditi; Kumar, Parimala; Nishana, Fathimath (International Journal of Research in Medical Sciences, 2017)
Methicillin-resistant Staphylococcus aureus (MRSA) is a type of staphylococcus bacteria that is resistant to certain antibiotics, including methicillin, penicillin and amoxicillin. For decades, MRSA primarily has affected people who are immunocompromised, such as patients in hospitals and long-term care facilities. Recently, it has been detected in otherwise healthy people. These infections typically show up as skin infections, like abscesses or boils. Less often, these infections can be more severe, causing pneumonia, sepsis or other potentially life-threatening infections. Most of the MRSA infections are of skin origin in the community. Its main mode of transmission is through the hands i.e., of the health care workers. So, hand washing is the most crucial factor in preventing the spread of infection. In a treatment area, the dental chair including the seat and arm rest, floor beneath the chair, sink, towel dispenser, counter top, and suction chamber remain the sources of infection. These usually are not directly contacted with the patient. Other routes of transmission of MRSA include body fluid exposure to non-intact skin of health care personnel, mucous membranes, or through the sharp or percutaneous injuries. In dentistry, MRSA is known to colonize the saliva and so considered as potentially infected material and often contains blood. The present case report is to create awareness about MRSA transmission, as well as infection prevention and control measures for dental practitioners.